PENERAPAN ANGGARAN BELANJA DENGAN PENDEKATAN KINERJA (PERFORMANCE BUDGET) PADA PENGELOLAAN KEUANGAN PROVINSI BALI - Ketut Ayuningsasi, Anak Agung (INPUT Jurnal Ekonomi dan Sosial, 2012)
Logical consequence of the implementation of regional autonomy causes changes in the regional financial management. The changes, among others, are the needs for budgeting reform, that is, from the traditional budget to performance budget. Performance budget very emphasizing at concept of value for money that is economic, efficiency, and effectiveness principle. This article aims to know the implementation of performance budget in Bali Province. It analized the allocation of regional expenditure after the implementation of performance budget. Before the application of budgeting with the performance approach, the implementation of regional budgeting in the Bali Province shows lack of efficiency in the use of budget. This is indicated by the higher routine expenditure compared with the expenditure for development with relatively high allocated miscellaneous expenditure. Through the implementation of performance budget, hopefully the regional expenditure allocated for development is higher than routine consumption. It means that government concerned in public money, so they can accomplish their main function which is to improve public welfare.
Keywords: regional expenditure, performance budget, traditional budget